(untitled) (Boston, MA, 1992)
This book summarizes our understanding of crucial events the shaped the development of the earth's environment and the course of biological evolution over some four billion years of geologic time. Several chapiters present new data and new syntheses, or summarize results of new types of analysis, material not usually available in current college textbooks, and some of them are broadly multidisciplinary, calling on data from diverse areas of science
Keywords: Evolution ( biology ),Paleontology; Congresses